2022
DOI: 10.1111/jonm.13712
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of US nurses and nurse leaders on authentic nurse leadership, healthy work environment, intent to leave and nurse well‐being during a second pandemic year: A cross sectional study

Abstract: Aim The main aim of this study was to determine the perceptions of clinical nurses and nurse leaders about authentic nurse leadership, work environment, pandemic impact, well‐being and intent to leave their position and profession during the second year of the pandemic. Background This research team studied the variables pre‐pandemic and in year one of the pandemic. As the pandemic continued, subsequent reports of workforce instability, deteriorating work environment and vulnerable well‐being called for an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 32 publications
3
39
2
Order By: Relevance
“…Regarding nurse outcomes, the findings of this study revealed that one-third of respondents were considering leaving their current workplace; the figure was comparable to or slightly better than those of previous studies, which reported that about 40 to 50 per cent of staff nurses intended to leave their current workplace in Taiwan and the United States [ 19 , 20 , 31 ]. This can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Regarding nurse outcomes, the findings of this study revealed that one-third of respondents were considering leaving their current workplace; the figure was comparable to or slightly better than those of previous studies, which reported that about 40 to 50 per cent of staff nurses intended to leave their current workplace in Taiwan and the United States [ 19 , 20 , 31 ]. This can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 69%
“…Researchers examined the associations between nurse outcomes and their practice environment, and noted that “dissatisfaction with management” is the top-ranked factor leading to the intention of nurses to leave their workplace [ 19 ]. They emphasized the role of nurse managers in rebuilding the nursing work environment and retaining nurses and stressed that there is an urgent need to further explore issues related to the competencies of nurse managers and nurse outcomes in light of the pandemic [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher transition shock in nurses who intend to leave their profession may be explained by a professional overload, inadequate working aspects, and higher personal and professional COVID-19 stressors, which all have an impact on their personal life. This could be a result of the transition or a toxic workplace environment, endangering the nurse’s well-being and disrupting their mental health [ 20 ]. However, inadequate working conditions and aspects of the organizational climate are cited by more than half of nurses who say they wished to leave nursing prior to the pandemic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transitioning to work in COVID-19 departments may cause the nurses to worry over spreading the virus to their own family and, combined with other significant professional stressors at work, might make transitioning difficult, disturb professional harmony, and increase their desire to leave the nursing field. Studies confirm that during the COVID-19 pandemic, there was increased intent for the nurses to leave their profession [ 19 , 20 , 21 ]. However, previous studies related to the transition mostly identify moving from the role of a student to the role of an employee, where there is a mismatch between personal expectations and the reality in clinical practice [ 10 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing pandemic‐related stress has led to a higher exodus rate of healthcare workers from the profession, which, in turn, has the potential to create an unstable workforce (Rangachari & Woods, 2020; Shah et al, 2021). Nurse managers’ well‐being is a critical element of a secure workforce (Raso et al, 2022). During the pandemic, nurse managers in hospital settings have been standing in the gaps between bedside nurses and administrators, trying to secure the processes of care delivery.…”
Section: Introductionmentioning
confidence: 99%